STRATEGI POLITICAL BRANDING PARTAI DEMOKRASI INDONESIA PERJUANGAN (PDI-P) DI MEDIA SOSIAL INSTAGRAM @PDIPERJUANGAN PADA TAHUN 2022 - Allymatul (2023)
This study aims to determine the PDI Perjuangan Party's political branding strategy on the social media Instagram @pdiperjuangan in 2022. Since the implementation of the multiparty system in Indonesia, parties have competed with each other to fight for power. This of course makes intense competition between political parties. So the party needs a strategy in capturing vote support. This research examines the political branding strategy of the Indonesian Democratic Party of Struggle (PDI-P) on the social media Instagram @pdiperjuangan in 2022 using the netnographic research method with primary and secondary data sources. Interview data collection techniques and literature review in the form of books, news, and previous research journals that are relevant to this research. There is a conformity of the strategy carried out by PDI-P with the theory of Political Branding in capturing votes. PDI-P is the only party in the reformation election era that has succeeded in winning the Legislative and Presidential Elections twice in a row in 2014 & 2019 and has always excelled in every electability survey of political parties in Indonesia. Pich & Newman's political branding theory is used to explain the political strategy carried out by PDI-P on Instagram social media. The results of the study show that the political branding strategy carried out by PDI-P on Instagram @pdiperjuangan has a strong relationship in increasing engagement between voters and parties. This can be seen from the response of the people who commented on Instagram @pdiperjuangan, most of whom tended to be positive about PDI-P posts. Keywords: Political Branding Strategy, PDI Perjuangan, Social Media Instagram